The Feasibility of Kopikaya Learning Media (Smart Box of Cultural Diversity) to Improve the Learning Outcomes of Grade V Elementary School Students - Putri, Farah Fauziyah Dila; Fatimah, Iis Daniati (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
Education is a conscious and planned effort to create an active and conducive learning process so that students are able to develop their potential optimally. One important instrument in education is the curriculum, including the Independent Curriculum which encourages the use of technology and learning innovation. However, observations at SDN Baturetno 1 show that learning is still conventional and does not utilize innovative media, resulting in low learning outcomes, especially in the material "Indonesian Cultural Diversity". This study aims to develop KOPIKAYA (Cultural Diversity Smart Box) learning media in the form of interactive game-based 3D media containing instructions for use, illustrated materials, and educational games to improve the learning outcomes of fifth-grade elementary school students. The research method used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. Validation was carried out by material experts, language experts, and media experts with the results of validity percentages of 82.2%, 86%, and 88%, respectively, which are included in the valid category. Based on the validator's suggestions, improvements were made to the font size, image clarity, and material coating. The results showed that KOPIKAYA media is suitable for use and can improve student motivation, understanding, and learning outcomes. Therefore, KOPIKAYA can be an alternative, innovative learning medium that supports the achievement of more optimal learning outcomes.